2021
DOI: 10.20396/san.v28i00.8661200
|View full text |Cite
|
Sign up to set email alerts
|

(In)segurança alimentar e nutricional de residentes em moradia estudantil durante a pandemia do covid-19

Abstract: Objetivos: avaliar a prevalência da insegurança alimentar e nutricional e fatores associados de estudantes, moradores do Conjunto Residencial da Universidade de São Paulo - CRUSP. Métodos: este estudo transversal avaliou por meio de questionário virtual 84 estudantes no período de junho a julho de 2020. Utilizou-se a versão curta (7 questões) da Escala Brasileira de Insegurança Alimentar para definição da variável desfecho: Insegurança Alimentar (IA). Variáveis sociodemográficas e econômicas, e questões relaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Data from our study indicated that undergraduates also represent a vulnerable population to food insecurity, with 38.6% experiencing any kind of food insecurity. This value could be even higher if only those students living in campus were studied, as was the case of the study from Araujo et al [15], where food insecurity was present in 84.5% of the students.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Data from our study indicated that undergraduates also represent a vulnerable population to food insecurity, with 38.6% experiencing any kind of food insecurity. This value could be even higher if only those students living in campus were studied, as was the case of the study from Araujo et al [15], where food insecurity was present in 84.5% of the students.…”
Section: Discussionmentioning
confidence: 84%
“…The scale has excellent cost effectiveness and has been used in several studies [15,[26][27][28][29]. Its application and analysis have shown that there are common aspects to the different socio-cultural contexts of food insecurity represented in the scale, including (1) psychological component-anxiety or doubt about future availability of food in the house to meet the needs of residents; (2) food quality-impairment of socially established preferences about food and its variety at home; (3) quantitative reduction of food among adults; (4) quantitative reduction of food among children; and (5) hunger-when someone goes without food all day due to lack of money to buy food [30][31][32].…”
Section: Food Insecuritymentioning
confidence: 99%
See 1 more Smart Citation
“…Paula e Zimmermann (2021) argumentam que tal situação não é resultado único da pandemia, mas desdobramento da progressiva contenção de investimentos em políticas públicas de proteção social em uma conjuntura de grave crise sanitária, social e econômica. Este quadro impactou sobremaneira os segmentos sociais mais vulneráveis, a exemplo dos universitários atendidos por programas de assistência estudantil (Araújo, Medeiros, Vasconcelos, & Dutra 2021). Desta forma, de acordo com Paula e Zimmermann (2021), torna-se imperativo o resgate do protagonismo do Estado e da priorização de políticas públicas de educação, de proteção social e de mecanismos de distribuição de renda.…”
Section: Principais Estressoresunclassified
“…Thus, evaluating diet quality is important in undergraduates. Also, many university students depend on meals offered by University Restaurants, which had their activities suspended during the COVID-19 lockdowns ( 10 ) The validated diet quality scale (ESQUADA) evaluates diet in a broader context, including the consumption of fresh, minimally processed, and ultra-processed foods and dietary practices (such as cooking, and substituting meals for snacks) ( 11 ). Thus, using this instrument could give important light on assessing diets and policy planning for undergraduates.…”
Section: Introductionmentioning
confidence: 99%